Kesalahan Mekanisme Pemungutan Pajak Pertambahan Nilai - Sri Hanggana (InFestasi, 2017)
The purpose of this study is to find the mistake of the PPN collection according to UU No. 42 th 2009 about alteration of UU No. 8 th 1983 about PPN and PPnMB. The mistake is caused the low of payment of PPN. Hanggana (2008) concluded that 97% businessmen choose manipulation strategy on PPN. Those mistakes are (1) pushing constumer to not pay PPN so the cost is lower, do not break the law, no punishment, and available in the same place, (2) customer who pay PPN can not control the flow of money to the government, (3) pushing the entrepreneuer not become a PKP in order to low the cost, (4) pushing entrepreneuer to take PPN without fee, but there is a punishment, jail and fine, (5) entrepreneuer need large capital to pay PPN in, (6) if all entrepreneuer are tax-abiding, then the small entrepreneuer and non-PKP entrepreneuer are passed the tax-abiding one’s, (7) tax-abiding entrepreneuer because of high cost, (8) tax-abiding entrepreneuer become bangkrupt, (9) entrepreneuer who manipulate tax will be bangkrupt because of paying fine and jailed, (10) the existing entrepreneuers are they who manipulated tax, but not jailed, (11) entrepreneuer who manipulate PPN should manipulate PPh for earnings and wages.